Skip to the end - James, Molly, 1967- (Forever, 2023)
"Amy Daniels has a pretty nice life. Her career is on the up, she loves her friends, and she's about to buy her very own flat. On a good day, Amy could be described as a catch--so why is she perpetually single? The trouble is, Amy can see something no one else can: the end. As soon as she kisses someone, she knows, in intimate, vivid detail, how their relationship will finish. A screaming argument in the middle of the supermarket over milk. An explicit email sent to the wrong address. A hasty escape through a bathroom window on the second date. At the altar-runaway-bride style. There seems to be no end to the unhappy endings. After years of trying, and failing, to change a pre-written future, Amy has given up. But then she drunkenly kisses three men at her best friend's wedding and sees three possible endings: two painful, one perfect. The problem is, Amy can't really remember who she kissed, and worse, what ending belongs to which person--the only thing she knows for certain is that she's determined to find out.."--